Effects of plyometric jump training on running economy in endurance runners: A systematic review and meta-analysis - Dudagoitia Barrio, E.; Fernández-Landa, J.; Negra, Y.; Ramirez-Campillo, R.; García de Alcaraz, A. (Kinesiology, 2023)
Running economy (RE) has a strong relationship with distance running performance and is defined as the energy demand for a given velocity. Plyometric jump training may improve RE. The present study aimed to assess the effects of plyometric jump training on endurance runners` running economy and to estimate the effectiveness of program duration, training frequency, total sessions, age, training status and velocity. A literature search was performed using PubMed/MEDLINE, Web of Science, and SCOPUS databases. Subgroup and single training factor analyses of program duration, frequency, total sessions, chronological age, training status, and running velocity were performed. A random-effects model for meta-analyses was used. Eighteen studies were selected for the systematic review and 10 for the meta-analysis. A trivial effect was noted for plyometric jump training on running economy (ES=0.19). However, plyometric jump training combined with resistance training revealed a large effect on running economy (ES=1.34). Greater running economy improvements were noted after training interventions with >15 total sessions (ES=1.00), >7 weeks (ES=0.95) and >2 days/week (ES=0.89). The youngest (ES=0.95) and highly trained participants (ES=0.94) with faster velocities (ES=0.95) obtained better results. Our findings highlight the effect of plyometric jump training that may improve running economy, particularly in combination with resistance training, after longer-term interventions (i.e., >15 total sessions, >7 weeks), with greater frequency, and among younger and more highly trained runners, especially during running at higher competitive velocities.